What recently graduated podiatrists think of rural work, and how services are responding: a qualitative study - Anna Couch; Jenni White; Belinda O'Sullivan; Terry Haines; Hylton Menz; Cylie Williams (James Cook University, 2022)
Introduction: Access to healthcare services should be equitable no matter where you live. However, the podiatry needs of rural populations are poorly addressed, partly because of workforce maldistribution. Encouraging emerging podiatrists to work in rural areas is a key solution. The aims were to explore (1) recently graduated podiatrists' perceptions regarding working rurally and (2) broader industry views of the factors likely to be successful for rural recruitment and retention. Methods: Recruitment for interviews pertaining to podiatrist recruitment and retention was conducted during 2017. Recruitment was through social media, podiatry professional association newsletters, public health podiatry emails. Graduate perceptions were explored via two focus groups of Australian podiatrists enrolled in the Podiatrists in Australia: Investigating Graduate Employment longitudinal survey. Industry views were explored through semistructured interviews with podiatry profession stakeholders. Inductive thematic analysis was used to analyse data about the perceptions of recently graduated podiatrists and stakeholders and the themes were triangulated between the two groups. Results: Overall, 11 recent graduate podiatrists and 15 stakeholders participated. The overarching themes among the two groups were the importance of 'growing me' and 'growing the profession'. Three superordinate themes were generated through analysis of both datasets, including (i) building a career, (ii) why I stay, and (iii) it cannot be done alone. Conclusion: This study identified that recently graduated podiatrists are likely to be attracted to rural work and retained in rural areas if they foresee opportunities for career progression in stable jobs, have a background of training and living in rural areas, like the lifestyle, and are able to access appropriate professional and personal supports. Building employment that spans public and private sector opportunities might be attractive to new graduate podiatrists seeking a breadth of career options. It is also important to recognise rural generalist podiatrists for any extended scope of services they provide along with raising public awareness of the role of rural podiatrist as a core part of multidisciplinary rural healthcare teams. Future training and workforce planning in podiatry must promote podiatrists taking up rural training and work so that maldistribution is reduced.